Presentations for Emerging Trends in the Global Soybean Complex - Yang, Di; Hitchner, Joanna; Cooper, Darren; Costa, Ramiro (2023)
Global changes in soybean production and consumption are reshaping global markets. Global oilseed prices have fallen considerably since last year’s record highs. World soybean production is likely to hit a record high in 2023/24, with global ending stocks projected to rebuild for the second consecutive year. Global soybean trade continues to be driven by China, which accounts for about 60% of total soybean imports. China’s domestic consumption has grown at about 4% per year over the past 10 years. In the United States, increased biodiesel production has diverted more soybean production to be crushed domestically for soybean oil, reducing soybean exports. As a result, Brazil and other suppliers have seen their market shares grow. In 2023/24, Brazil is projected to account for almost 58% of total soybean exports.